Estuviste bien, Pirulo (tango, 1930) - García Brunelli, Omar (Universidad Nacional del Litoral, 2021)
Summary This paper analyzes the tango Estuviste bien, Pirulo, composed in 1930 by S. Piana, with lyrics by R. Cordone and C. Goicochea. As a humorous tango it belongs to a long tradition of pieces that exploit a comic style. The lyric is about a woman who reproaches her partner for abandonment, in an ironic tone accentuated by the use of lunfardo. Among the three versions that were recorded, one corresponds to A. Maizani and the other two to the singer R. Maida, one as a chorus player in the P. Maffia orchestra, and the other as a soloist accompanied by the A. Castellanos orchestra. When the interpreter is the male singer, we find an additional parodic mechanism that is not present in the female version. And in the Maffia orchestra recording, moreover, the parody tone extends to the very composition of the bandoneon solo of the orchestra director, which is studied in detail in the context of the solos and the role of the bandoneons in the orquesta típica between 1923 and the early 1930s, as well as among Maffia's own solos during the same period.